Cardiac Amyloidosis Presenting as Biventricular Systolic Heart Failure. (2nd April 2021) - Oye, Monique; Richardson, Aaron; Sadic, Edin; Alkhasawneh, Ahmad; Velarde, Gladys
Abstract : A previously healthy octogenarian presented with new onset heart failure symptoms. Comprehensive multimodality imaging including complete echocardiography with longitudinal strain analysis, cardiac magnetic resonance imaging (cMRI), nuclear medicine pyrophosphate (99-mcTcPYP) scan along with biomarker, monoclonal protein analysis, and fat pad biopsy confirmed diagnosis of transthyretin cardiac amyloidosis.